Lessons learned from the upscaling of an iron bio-oxidation process to improve uranium recovery - Hubau, Agathe; Bru, Kathy; Idrissa Oumarou, Safiatou; Leycuras, Cécile (Comptes Rendus. Chimie)
This study presents the various steps performed for the industrial implementation of a process dedicated to the bio-oxidation of the ferrous iron contained in the solution used to leach uranium with the objective of increasing its recovery. These steps included theoretical works, laboratory-scale tests on synthetic effluents and laboratory- and pilot-scale tests on industrial effluents at the mining site. The main results from each of these steps are presented as well as the challenges that have to be addressed for the integration of this process into the existing flowsheet. They allowed to get insights into the upscaling of a biotechnology at an industrial scale.